Triallyl isocyanurate polymer, its production method, curable composition and polymer molded product
Patent Information
- Application Number
- JP2021021049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-18
- Filing Date
- 2021-02-12
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-12
AI Technical Summary
【0007】 本発明によれば、液状であって基材への塗布又は含侵が可能であり、揮発性が抑制されたトリアリルイソシアヌレート重合体、その製造方法、硬化性組成物及び高分子成形体を提供できる。さらに、本発明により得られるトリアリルイソシアヌレート重合体及び高分子成形体は、トリアリルイソシアヌレートと同等の誘電率を維持したまま、耐熱性にも優れるものである。
Smart Images

Figure 0007639383000019 
Figure 0007639383000020 
Figure 0007639383000021
Abstract
Description
[Technical field]
[0001] The present invention relates to a triallyl isocyanurate polymer, a method for producing the same, a curable composition, and a polymer molded article. [Background technology]
[0002] Triallyl isocyanurate (hereinafter sometimes referred to as "TAIC") has the advantageous property that it is liquid and can be blended with, applied to, or impregnated into resins, and is known as a crosslinking agent for crosslinkable polymers such as crosslinkable elastomers or crosslinkable thermoplastic resins (Patent Document 1, Patent Document 2). TAIC may be used by impregnating a prepreg or by kneading it into a crosslinkable polymer (Patent Document 3). When TAIC is used by impregnating a prepreg, TAIC may volatilize when the prepreg is heated and pressed to form. When TAIC is used by kneading it into a crosslinkable polymer, TAIC may volatilize during storage for several days between mixing TAIC and the crosslinkable polymer and crosslinking treatment. In either case, TAIC volatilization prevents the expected crosslinking performance from being exhibited. On the other hand, a radical polymerization method is known as a polymerization method for TAIC (Patent Document 4, Patent Document 5). It has also been reported that a TAIC dimer can be synthesized by organic chemical techniques, for example, by reacting the sodium salt of 1,3-diallyl isocyanurate with 1,4-dichloro-2-butene (Patent Document 6 and Patent Document 7). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-118536 A [Patent Document 2] Patent No. 5852234 [Patent Document 3] Patent No. 4228568 [Patent Document 4] Patent No. 2782358 [Patent Document 5] Patent No. 2889971 [Patent Document 6] Japanese Patent Application Publication No. 54-103881 [Patent Document 7] JP 2015-151413 A Summary of the Invention [Problem to be solved by the invention]
[0004] One possible way to suppress the volatility of TAIC while maintaining its liquid form and its ability to be applied or impregnated is to oligomerize TAIC. However, in the radical polymerization reactions described in Patent Documents 4 and 5, it is difficult to control the reaction, so that a high molecular weight solid polymer is obtained, and it is difficult to obtain a liquid TAIC oligomer. In addition, the high-purity TAIC dimer described in Patent Documents 6 and 7 is a solid with a melting point of 125° C., and cannot be applied or impregnated. In addition, in order to isolate the TAIC dimer from the reaction product, complicated and industrially disadvantageous steps such as filtration and recrystallization are required.
[0005] The present invention has been made to solve the above problems, and an object of the present invention is to provide a triallyl isocyanurate polymer that is liquid and can be applied to or impregnated into a substrate, and has reduced volatility, a production method thereof, a curable composition, and a polymer molded product. [Means for solving the problem]
[0006] [1] Triallyl isocyanurate polymer that is liquid at 30°C and has a viscosity of 300 mPa·s or more at 30°C. [2] Triallyl isocyanurate polymer having a polystyrene-equivalent weight average molecular weight (Mw) of 480 or more as measured by gel permeation chromatography. [3] Measured at 30°C using deuterated chloroform as the solvent. 1 The triallyl isocyanurate polymer according to [1] or [2], in which signals (peaks) are observed at 4.5 to 5.0 ppm and 5.4 to 5.8 ppm in a H-NMR spectrum. [4] A triallyl isocyanurate polymer comprising a structural unit represented by formula (1). [ka] In formula (1), * represents a bonding point. [5] The triallyl isocyanurate polymer according to any one of [1] to [4], having a structure represented by formula (2): [ka] In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom, m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; L 1 represents a tetravalent linking group containing two divalent linking groups derived from double bonds or carbon-carbon double bonds when n≠0, and represents a divalent group represented by formula (a) when n=0. [ka] In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, R 9 and R 10 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom. [6] A triallyl isocyanurate polymer represented by formula (2): [ka] In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom, m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; L 1 represents a tetravalent linking group containing two divalent linking groups derived from double bonds or carbon-carbon double bonds when n≠0, and represents a divalent group represented by formula (a) when n=0. [ka] In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, R 9 and R 10 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom. [7] The method for producing a triallyl isocyanurate polymer according to any one of [1] to [6], comprising polymerizing triallyl isocyanurate by an olefin metathesis reaction. [8] A curable composition comprising the triallyl isocyanurate polymer according to any one of [1] to [6] and a crosslinkable polymer. [9] A polymer molded article obtained by curing the curable composition according to [8]. Effect of the Invention
[0007] According to the present invention, there can be provided a triallyl isocyanurate polymer which is liquid and can be applied to or impregnated into a substrate, and has reduced volatility, a method for producing the same, a curable composition, and a polymer molded article. Furthermore, the triallyl isocyanurate polymer and polymer molded article obtained by the present invention have excellent heat resistance while maintaining a dielectric constant equivalent to that of triallyl isocyanurate. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a 1H NMR spectrum of the TAIC polymer of Example 1. [Diagram 2] FIG. 2 is a 1H NMR spectrum of the TAIC polymer of Example 2. [Diagram 3] FIG. 3 is a 1H NMR spectrum of the TAIC polymer of Example 3. [Figure 4] FIG. 4 is a 1H NMR spectrum of the TAIC polymer of Example 4. [Diagram 5] FIG. 5 is a 1H NMR spectrum of the TAIC polymer of Example 5. [Figure 6] FIG. 6 is a 1H NMR spectrum of the TAIC polymer of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] "TAIC" means triallyl isocyanurate. "TAIC dimer" means a dimer of triallyl isocyanurate obtained by reacting the sodium salt of 1,3-diallyl isocyanurate with 1,4-dichloro-2-butene. The term "TAIC polymer" refers to a triallyl isocyanurate polymer. In the present invention, the term particularly refers to a triallyl isocyanurate polymer obtained by polymerizing triallyl isocyanurate through an olefin metathesis reaction. The compound from which the structural units of a polymer are derived is called a monomer. Numerical ranges expressed using "~" include both end values. "GPC" is an abbreviation for Gel Permeation Chromatography. The mass average molecular weight (Mw) and number average molecular weight (Mn) of the compound are molecular weights measured by GPC and calculated as standard polystyrene. The molecular weight of a compound that has a single molecular weight and no molecular weight distribution is expressed by a formula weight.
[0010] [Trialyl isocyanurate polymer] <First aspect> A first embodiment of the TAIC polymer of the present invention is a TAIC polymer that is liquid at 30°C and has a viscosity at 30°C of 300 mPa·s or more.
[0011] Melting Point The TAIC polymer of this embodiment is liquid at 30°C, and therefore has a melting point below 30°C. The melting point of the TAIC polymer of this embodiment is usually less than 30°C, preferably less than 25°C, more preferably less than 20°C, even more preferably less than 15°C, and even more preferably less than 5°C. Since the TAIC polymer of this embodiment is a liquid, it can be impregnated into or coated on a sheet-like substrate such as a prepreg containing a crosslinkable polymer, and is therefore easy to handle.
[0012] 《Viscosity (30℃)》 The viscosity of the TAIC polymer of this embodiment at 30°C is 300 mPa·s or more, preferably 400 mPa·s or more, more preferably 1000 mPa·s or more, and even more preferably 4000 mPa·s or more. There is no particular upper limit to the viscosity. The viscosity is preferably 3,000,000 mPa·s or less, more preferably 750,000 mPa·s or less, and even more preferably 450,000 mPa·s or less. The viscosity is preferably 300 to 3,000,000 mPa·s, more preferably 400 to 750,000 mPa·s, and even more preferably 4,000 to 450,000 mPa·s. The viscosity is measured using a cone-plate viscometer at 30° C. using the TAIC polymer of this embodiment without using any solvent. Details of the viscosity measurement method will be described in the examples below. The fact that the viscosity at 30°C can be measured means that the TAIC polymer of this embodiment is a liquid at 30°C.
[0013] When the viscosity is 300 mPa·s or more, the molecular weight (mass average molecular weight) of the TAIC polymer of this embodiment is greater than the molecular weight (formula weight) of the TAIC dimer obtained by radical polymerization, and volatility is suppressed. When the viscosity is 3,000,000 mPa·s or less, the polymer can be impregnated into or coated on a sheet-like substrate such as a prepreg, and the polymer has excellent handleability.
[0014] Other physical properties (mass average molecular weight) The mass average molecular weight of the TAIC polymer of this embodiment is usually 480 or more, preferably 500 to 2000, more preferably 500 to 1500, and even more preferably 500 to 1000. Details of the method for measuring the mass average molecular weight will be described in the examples described later.
[0015] (Volatile) The volatility of the TAIC polymer of this embodiment is evaluated by performing thermogravimetric analysis using a thermogravimetric differential thermal analyzer (TG-DTA) to determine the weight loss rate. The details of the method for measuring the weight loss rate will be described in the Examples below. The weight loss rate of the TAIC polymer of this embodiment by thermogravimetric analysis is preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, and even more preferably 20% or less. If the weight loss rate is 50% or less, it can be evaluated that volatility is sufficiently suppressed.
[0016] (Heat resistance) The heat resistance of the TAIC polymer of this embodiment is evaluated by performing thermogravimetric analysis using a thermogravimetric differential thermal analyzer (TG-DTA) to determine the thermal decomposition temperature. The details of the method for measuring the thermal decomposition temperature will be described in the examples below. The thermal decomposition temperature of the TAIC polymer of this embodiment is preferably not less than 400° C. Since the heat press temperature of a prepreg is usually about 200° C., if the thermal decomposition temperature of the TAIC polymer is not less than 400° C., it can be evaluated as having sufficient heat resistance.
[0017] (Dielectric constant, dielectric tangent) The dielectric constant and dielectric dissipation factor of the cured product obtained by curing the TAIC polymer of this embodiment are preferably 70 to 130% of the dielectric constant and dielectric dissipation factor of the cured product obtained by curing TAIC. When the dielectric constant and dielectric dissipation factor are 70 to 130% of those of TAIC, it becomes easier to replace conventionally used TAIC with the TAIC polymer of this embodiment without making a major change to the work process. The dielectric constant and dielectric dissipation factor of the cured product are values measured at 2 MHz by the automatic balancing bridge method. Details of the method for measuring the dielectric constant and dielectric dissipation factor will be described in the examples below.
[0018] "structure" The TAIC polymer of this embodiment preferably contains a constitutional unit represented by formula (1). The TAIC polymer of this embodiment is different from the TAIC prepolymer synthesized by the conventional radical polymerization method in that the TAIC units are bonded to each other via a carbon-carbon double bond, and therefore the TAIC polymer of this embodiment has excellent crosslinkability similar to that of TAIC.
[0019] [ka]
[0020] In formula (1), "*" represents a bonding point. At the attachment points, a structural unit or an end group of the TAIC polymer of this embodiment is attached. Of all the structural units constituting the TAIC polymer of this embodiment, the proportion of the structural units represented by formula (1) is preferably 50 mol% or more, more preferably 65 mol% or more, even more preferably 80 mol% or more, even more preferably 95 mol% or more, and particularly preferably 100 mol%.
[0021] The TAIC polymer of this embodiment more preferably has a structure represented by formula (2). [ka]
[0022] In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom, m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; L 1 represents a tetravalent linking group containing two divalent linking groups derived from double bonds or carbon-carbon double bonds when n≠0, and represents a divalent group represented by formula (a) when n=0.
[0023] [ka]
[0024] In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, R 9 and R 10 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom.
[0025] L 1 and L 2 Regarding the above, the tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond may be, for example, a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond derived from a TAIC monomer.
[0026] R 1 , R 2 , R 3 , R 4 , R5 , R 6 , R 7 , R 8 , R 9 and R 10 depends on the method of preparation of the TAIC polymer. For example, R 1 , R 3 , R 5 , R 7 and R 9 is at the same time a hydrogen atom or a hydrocarbon group which may contain a heteroatom, and R 2 , R 4 , R 6 , R 8 and R 10 However, at the same time, it may be a hydrogen atom.
[0027] <Second aspect> A second embodiment of the TAIC polymer of the present invention is a TAIC polymer having a polystyrene-equivalent weight average molecular weight (hereinafter simply referred to as "weight average molecular weight") of 480 or more as measured by GPC.
[0028] 《Mass average molecular weight》 The mass average molecular weight of the TAIC polymer of this embodiment is 480 or more, preferably 500 to 2000, more preferably 500 to 1500, and even more preferably 500 to 1000. Details of the method for measuring the mass average molecular weight will be described in the examples described later. The TAIC polymer of this embodiment has a mass average molecular weight of 480 or more, and therefore contains a compound with a molecular weight larger than the molecular weight (formula weight) of the TAIC dimer obtained by radical polymerization, and has reduced volatility.
[0029] Other characteristics (Melting Point) The melting point of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the melting point and the advantageous effects are also similar.
[0030] (Viscosity (30℃)) The viscosity of the TAIC polymer of this embodiment at 30°C is usually 300 mPa·s or more, preferably 400 mPa·s or more, more preferably 1000 mPa·s or more, and even more preferably 4000 mPa·s or more. There is no particular upper limit to the viscosity. The viscosity is preferably 3,000,000 mPa·s or less, more preferably 750,000 mPa·s or less, and even more preferably 450,000 mPa·s or less. The viscosity is preferably 300 to 3,000,000 mPa·s, more preferably 400 to 750,000 mPa·s, and even more preferably 4,000 to 450,000 mPa·s. The viscosity is measured using a cone-plate viscometer at 30° C. using the TAIC polymer of this embodiment without using any solvent. Details of the viscosity measurement method will be described in the examples below.
[0031] (Volatile) The volatility of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the weight loss rate and the advantageous effects are also similar.
[0032] (Heat resistance) The heat resistance of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the thermal decomposition temperature and the advantageous effects are also similar.
[0033] (Dielectric constant, dielectric tangent) The dielectric constant and dielectric dissipation factor of the cured product obtained by curing the TAIC polymer of this embodiment are similar to those of the cured product obtained by curing the TAIC polymer of the first embodiment described above, and the preferred ranges of the dielectric constant and dielectric dissipation factor and advantageous effects are also similar.
[0034] "structure" The TAIC polymer of this embodiment, like the TAIC polymer of the first embodiment described above, preferably contains a structural unit represented by the above formula (1), and more preferably has a structure represented by the above formula (2). The TAIC polymer of this embodiment is different from the TAIC prepolymer synthesized by the conventional radical polymerization method in that the TAIC units are bonded to each other via a carbon-carbon double bond, and therefore the TAIC polymer of this embodiment has excellent crosslinkability similar to that of TAIC.
[0035] <Third aspect> A third embodiment of the TAIC polymer of the present invention is a TAIC polymer containing a constitutional unit represented by the above formula (1). The TAIC polymer of this embodiment is different from the TAIC prepolymer synthesized by the conventional radical polymerization method in that the TAIC units are bonded to each other via a carbon-carbon double bond, and therefore the TAIC polymer of this embodiment has excellent crosslinkability similar to that of TAIC.
[0036] <Preferred Structure> The TAIC polymer of this embodiment preferably has a structure represented by the above formula (2).
[0037] 《Characteristics》 (mass average molecular weight) The weight average molecular weight of the TAIC polymer of this embodiment is similar to the weight average molecular weight of the TAIC polymer of the first embodiment described above, and the preferred range and advantageous effects of the weight average molecular weight are also similar.
[0038] (Melting Point) The melting point of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the melting point and the advantageous effects are also similar.
[0039] (Viscosity (30℃)) The viscosity of the TAIC polymer of this embodiment at 30° C. is similar to the viscosity of the TAIC polymer of the second embodiment described above at 30° C., and the preferred range of viscosity and advantageous effects are also similar.
[0040] (Volatile) The volatility of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the weight loss rate and the advantageous effects are also similar.
[0041] (Heat resistance) The heat resistance of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the thermal decomposition temperature and the advantageous effects are also similar.
[0042] (Dielectric constant, dielectric tangent) The dielectric constant and dielectric dissipation factor of the cured product obtained by curing the TAIC polymer of this embodiment are similar to those of the cured product obtained by curing the TAIC polymer of the first embodiment described above, and the preferred ranges of the dielectric constant and dielectric dissipation factor and advantageous effects are also similar.
[0043] <Fourth aspect> The fourth embodiment of the TAIC polymer of the present invention is a TAIC polymer represented by the above formula (2). The TAIC polymer of this embodiment is different from the TAIC prepolymer synthesized by the conventional radical polymerization method in that the TAIC units are bonded to each other via a carbon-carbon double bond, and therefore the TAIC polymer of this embodiment has excellent crosslinkability similar to that of TAIC.
[0044] 《Characteristics》 (mass average molecular weight) The weight average molecular weight of the TAIC polymer of this embodiment is similar to the weight average molecular weight of the TAIC polymer of the first embodiment described above, and the preferred range and advantageous effects of the weight average molecular weight are also similar.
[0045] (Melting Point) The melting point of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the melting point and the advantageous effects are also similar.
[0046] (Viscosity (30℃)) The viscosity of the TAIC polymer of this embodiment at 30° C. is similar to the viscosity of the TAIC polymer of the second embodiment described above at 30° C., and the preferred range of viscosity and advantageous effects are also similar.
[0047] (Volatile) The volatility of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the weight loss rate and the advantageous effects are also similar.
[0048] (Heat resistance) The heat resistance of the TAIC polymer of this embodiment is similar to that of the TAIC polymer of the first embodiment described above, and the preferred range of the thermal decomposition temperature and the advantageous effects are also similar.
[0049] (Dielectric constant, dielectric tangent) The dielectric constant and dielectric dissipation factor of the cured product obtained by curing the TAIC polymer of this embodiment are similar to those of the cured product obtained by curing the TAIC polymer of the first embodiment described above, and the preferred ranges of the dielectric constant and dielectric dissipation factor and advantageous effects are also similar.
[0050] [Method of producing triallyl isocyanurate polymer] The method for producing a TAIC polymer of the present invention is characterized by polymerizing a TAIC monomer by an olefin metathesis reaction.
[0051] The olefin metathesis reaction is a catalytic reaction in which the recombination of bonds occurs between two types of olefins. In the method for producing a TAIC polymer of the present invention, allyl groups react between TAIC monomers to form a new carbon-carbon double bond and one molecule of ethylene is eliminated. In the polymerization of TAIC monomers by the olefin metathesis reaction, one carbon-carbon double bond is formed from two carbon-carbon double bonds. In this respect, it differs from radical polymerization in which a carbon-carbon double bond is cleaved to form a carbon-carbon single bond. The fact that the TAIC units are bonded to each other via a carbon-carbon double bond means, in other words, that the TAIC polymer of the present invention has an internal olefin. The presence of this internal olefin can be observed using a nuclear magnetic resonance apparatus. Specifically, in a 1H-NMR spectrum measured at a measurement temperature of 30°C using deuterated chloroform as a solvent, signals (peaks) derived from the internal olefin are observed at 4.5 to 5.0 ppm and 5.4 to 5.8 ppm.
[0052] Examples of catalysts used in olefin metathesis reactions include compounds of transition metal elements such as molybdenum and tungsten (Schrock, RR, Hoveyda, AH, Molybdenum and Tungsten Imido Alkylidene Complexes as Efficient Olefin-Metathesis Catalysts, Angewandte Chemie International Edition, Vol. 42, No. 38, October 1, 2003, pp. 4592-4633). Polymerization catalysts obtained by reacting metal halides such as tungsten hexachloride, molybdenum pentachloride, tungsten oxytetrachloride, or molybdenum oxytetrachloride with organotin compounds or organoaluminum compounds can also be used (Ivin, KJ, Mol, JC, Olefin Metathesis and Metathesis Polymerization, Academic Press, San Diego, CA, 1997). Ruthenium transition metal compounds can also be used (Ogba, OM, Warner, NC, O'Leary, DJ, Grubbs, RH, Recent advances in ruthenium-based olefin metathesis, Chemical Society Reviews, Vol. 47, No. 12, May 1, 2018, pp. 4510-4544). Among these, molybdenum or tungsten compounds are preferred, molybdenum or tungsten imido complexes or oxo complexes are more preferred, molybdenum or tungsten imido complexes are more preferred, and M(NAr)(CHR11 )(OR 12 ) 2 In this formula, M represents molybdenum or tungsten, Ar represents an aryl group which may have a substituent, and R 11 and R 12 each independently represents a hydrocarbon group which may contain a heteroatom.
[0053] In carrying out the polymerization reaction, a vinyl compound or a diene compound may be added to the polymerization system in order to adjust the molecular weight of the resulting TAIC polymer. The vinyl compound is not particularly limited as long as it is an organic compound having a vinyl group, and examples thereof include 1-butene, 1-pentene, 1-hexene, 1-octene, and styrene. The diene compound is not particularly limited as long as it is an organic compound having two double bonds, and examples thereof include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,6-heptadiene, 2-methyl-1,4-pentadiene, 2,5-dimethyl-1,5-hexadiene, 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and 1,3-hexadiene.
[0054] The TAIC polymer of the present invention is preferably produced by dissolving the raw material TAIC monomer in a solvent and stirring the solution while heating in the presence of a catalyst. The heating temperature is preferably 30° C. or higher, more preferably 35° C. or higher, in order to improve the reaction rate. The heating temperature is not particularly limited as long as it is lower than the boiling point of the solvent. For example, when toluene is used as the solvent, the heating temperature is preferably about 110° C. or lower, which is the boiling point of toluene under 1013 hPa. The intensity and duration of the stirring are not particularly limited. It is preferable to stir so that the formation of the TAIC polymer proceeds sufficiently, and for example, the stirring time may be within the range of 10 minutes to 8 hours. The solvent is not particularly limited as long as it can dissolve or disperse the TAIC monomer. Examples of the solvent include toluene, hexane, dichloromethane, chloroform, and tetrahydrofuran, which are low cost and readily available.
[0055] [Curable composition] The curable composition of the present invention contains the above-mentioned TAIC polymer and a crosslinkable polymer. The crosslinkable polymer may be a polymer that has been conventionally crosslinked by TAIC. Examples of the crosslinkable polymer include epoxy resin, phenol resin, polyester resin, unsaturated polyester resin, polyamide resin, polyether ketone resin, polyether ether ketone resin, polyether ketone ketone resin, polyether ether ketone resin, polyphenylene ether resin, modified polyphenylene ether resin, vinyl chloride resin, polyolefin resin, acrylic resin, polystyrene resin, polycarbonate resin, polyacetal resin, fluororesin, and ethylene vinyl acetate copolymer resin. The curable composition of the present invention may further contain a crosslinking auxiliary, a reaction initiator, a filler, and the like. Examples of the crosslinking aid include TAIC, TAIC derivatives, trimethallyl isocyanurate, trimethallyl isocyanurate derivatives, triallyl cyanurate, and triallyl cyanurate derivatives. Examples of the reaction initiator include di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylperoxy-(2-ethylhexyl)carbonate, 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroxyperoxide, t-butyl-α-cumyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, 1,4-bis(t-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, benzoyl peroxide, and t-butylperoxybenzene. Examples of the filler include silica, carbon black, calcium carbonate, aluminum hydroxide, aluminum borate, zinc oxide, clay, barium sulfate, mica, talc, titanium oxide, alumina, and glass fiber.
[0056] [Polymer molded body] The polymer molded article of the present invention can be obtained by curing the above-mentioned curable composition of the present invention. The curable composition of the present invention can be cured, for example, by heating. As for the curing conditions, for example, a method in which the composition is pre-cured by heating at 100 to 150° C. for 1 to 10 minutes, and then fully cured by heating at 150 to 250° C. for 1 to 5 hours can be mentioned. EXAMPLES
[0057] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the examples described below, and various modifications are possible without departing from the gist of the present invention. In the following examples and comparative examples, an isopropyl group may be represented as "iPr", a methyl group as "Me", and a phenyl group as "Ph".
[0058] [Measurement method] <Viscosity (30℃)> The viscosity of the TAIC polymer was measured using a cone-plate viscometer (LVDV3T, manufactured by Brookfield Corp.) The measurement temperature was 30° C., and the TAIC polymer was not dissolved in a solvent, and the measurement was performed without a solvent. The viscosity of TAIC polymer 5 exceeded the measurement limit of the apparatus at a measurement temperature of 30°C, so the measurement was performed at a measurement temperature of 40°C.
[0059] <Mass average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn)> The TAIC polymer (approximately 5 mg) was placed in a glass vial, and approximately 5 g of reagent-grade chloroform (ethanol concentration = 0.3 to 1.0% by mass) containing ethanol as a stabilizer was added and allowed to stand overnight to prepare a sample solution with a concentration of approximately 0.1% by mass. The obtained sample solution was filtered through a 0.45 μm pretreatment filter (GL Science, Chromatodisk 13N) and then subjected to GPC measurement. Next, GPC measurement was performed using Showa Denko's Shodex HK-404L (4.6×150 mm, 3.5 μm) and Shodex HK-401 (4.6×150 mm, 3 μm) columns and Tosoh's HLC-8420GPC equipped with an RI detector. The measurement conditions were as follows: Sample injection volume: 20 μL Column temperature: 40℃ Elution solvent: Reagent grade chloroform Flow rate: 0.7mL / min The calculated average molecular weight was calculated as follows: Commercially available monodisperse polystyrene (Tosoh Corporation, F-128, 80, 40, 20, 10, 4, 2, 1, A-5000, 2500, 1000, 500) and BHT (molecular weight 220) were used as standard samples to prepare calibration curves relating the retention time and molecular weight of the polystyrene standard sample and BHT, and then the polystyrene-equivalent mass average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the TAIC polymer were calculated based on the calibration curve.
[0060] <Decomposition temperature (heat resistance)> The decomposition temperature was measured as follows. Using TG-DTA (differential thermobalance Thermo plus EVO2 TG-DTA manufactured by Rigaku Corporation), a sample (approximately 5 mg) was held at 30°C for 30 minutes, and then heated to 550°C at a rate of 10°C / min. The top of the endothermic peak observed when the sample was heated was taken as the decomposition temperature.
[0061] <Preparation of evaluation board> 70 parts by mass of modified polyphenylene ether resin (SABIC Innovation Plastics, SA9000; mass average molecular weight (Mw) = 1700; number of terminal hydroxyl groups: 2; terminal hydroxyl groups modified with methacrylic groups), 30 parts by mass of TAIC polymer, 1 part by mass of Perbutyl P (NOF Corporation, 1,3-bis(t-butylperoxyisopropyl)benzene), and 55 parts by mass of silica particles (Admatechs, SCJ2500-SVJ) were each charged into 104 parts by mass of toluene, and the mixture was stirred at 80°C for 60 minutes to completely dissolve, thereby preparing a varnish.
[0062] The prepared varnish was impregnated into glass cloth (Nittobo Co., Ltd., #2116E glass), and then heated and dried at 135°C for 5 minutes to prepare a prepreg. At that time, the content of components that constitute the resin by the curing reaction, such as the modified polyphenylene ether resin and the crosslinking aid, (resin content) was adjusted to about 50 mass%.
[0063] Four sheets of the prepared prepreg were stacked and heated and pressed at a temperature of 200° C. for two hours at a pressure of 3 MPa to prepare an evaluation board.
[0064] <Dielectric constant and dielectric tangent> The dielectric constant and dielectric loss tangent of the evaluation board were measured at 2 MHz by the automatic balancing bridge method (Precision LCR meter E4980A, manufactured by Keysight Technologies, Inc.).
[0065] <Volatile content (volatile)> The volatile content of the TAIC polymer in the prepreg was measured by TG-DTA (STA6000, manufactured by PerkinElmer Japan) at the pressing temperature of 200°C. The heating conditions were: heating rate 130°C / min from 30°C to 200°C, holding at 200°C for 30 minutes, and heating rate 200°C / min from 200°C to 800°C. The weight loss at 200°C was calculated as the prepreg volatile content W (200) The weight loss at 800°C is the total resin weight W (800) The volatile content of the TAIC polymer in the prepreg is W(200) / W (800) was requested as follows.
[0066] [Example 1] Synthesis of TAIC polymer Mo(N-2,6-iPr 2 C 6 H 3 )(CHCMe 2 Ph)(OCMe(CF 3 ) 2 ) 2 (11.3 mg, 0.0147 mmol) was weighed into a two-necked recovery flask, and toluene (3 mL) was added to prepare a catalyst solution. TAIC (19.1 g, 76.5 mmol) was weighed into another two-necked eggplant flask, toluene (20 mL) was added, and then tri-n-octylaluminum (0.075 mmol) was added and stirred to prepare a raw material solution. The catalyst solution was added to the raw material solution, and the mixture was stirred at 40°C for 8 hours. After stirring, benzaldehyde was added to the reaction solution to quench the reaction. After the reaction was stopped, toluene was distilled off under reduced pressure to obtain 18.7 g of a TAIC polymer (hereinafter referred to as "TAIC polymer 1") as a pale yellow viscous liquid.
[0067] <measurement> Using the above-mentioned measurement methods, the viscosity, mass average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn), decomposition temperature, dielectric constant, dielectric loss tangent, and volatile content of TAIC polymer 1 were measured. The results are shown in Table 1. 1 H NMR measurement results ( 1 1 H NMR spectrum) is shown in Figure 1.
[0068] [Example 2] Synthesis of TAIC polymer Mo(N-2,6-iPr 2 C 6 H 3 )(CHCMe 2 Ph)(OCMe(CF 3 ) 2 ) 2(50.0 mg, 0.0653 mmol) was weighed into a two-necked recovery flask, and toluene (3 mL) was added to prepare a catalyst solution. TAIC (32.7 g, 131 mmol) was weighed into another two-necked eggplant flask, toluene (5 mL) was added, and then tri-n-octylaluminum (0.070 mmol) was added and stirred to prepare a raw material solution. The catalyst solution was added to the raw material solution, and the mixture was stirred at 40° C. for 20 minutes. After stirring, benzaldehyde was added to the reaction solution to quench the reaction. After the reaction was stopped, toluene was distilled off under reduced pressure to obtain 24.8 g of a TAIC polymer (hereinafter referred to as "TAIC polymer 2") as a pale yellow viscous liquid.
[0069] <measurement> Using the above-mentioned measurement methods, the viscosity, mass average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn), decomposition temperature, dielectric constant, dielectric loss tangent, and volatile content of TAIC polymer 2 were measured. The results are shown in Table 1. 1 H NMR measurement results ( 1 1 H NMR spectrum) is shown in Figure 2.
[0070] [Example 3] Synthesis of TAIC polymer Mo(N-2,6-iPr 2 C 6 H 3 )(CHCMe 2 Ph)(OCMe(CF 3 ) 2 ) 2 (59.4 mg, 0.0776 mmol) was weighed into a two-necked recovery flask, and toluene (3 mL) was added to prepare a catalyst solution. TAIC (35.9 g, 144 mmol) was weighed into another two-necked eggplant flask, toluene (5 mL) was added, and then tri-n-octylaluminum (0.070 mmol) was added and stirred to prepare a raw material solution. The catalyst solution was added to the raw material solution, and the mixture was stirred at 40° C. for 40 minutes. After stirring, benzaldehyde was added to the reaction solution to quench the reaction. After the reaction was stopped, toluene was distilled off from the reaction vessel under reduced pressure to obtain 29.5 g of a TAIC polymer (hereinafter referred to as "TAIC polymer 3") as a pale yellow viscous liquid.
[0071] <measurement> Using the above-mentioned measurement methods, the viscosity, mass average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn), decomposition temperature, dielectric constant, dielectric loss tangent, and volatile content of TAIC polymer 3 were measured. The results are shown in Table 1. 1 H NMR measurement results ( 1 1 H NMR spectrum) is shown in Figure 3.
[0072] [Example 4] Synthesis of TAIC polymer Mo(N-2,6-iPr 2 C 6 H 3 )(CHCMe 2 Ph)(OCMe(CF 3 ) 2 ) 2 (60.3 mg, 0.0788 mmol) was weighed into a two-necked recovery flask, and toluene (3 mL) was added to prepare a catalyst solution. TAIC (35.7 g, 143 mmol) was weighed into another two-necked eggplant flask, toluene (5 mL) was added, and then tri-n-octylaluminum (0.070 mmol) was added and stirred to prepare a raw material solution. The catalyst solution was added to the raw material solution, and the mixture was stirred at 40°C for 50 minutes. After stirring, benzaldehyde was added to the reaction solution to quench the reaction. After the reaction was stopped, toluene was distilled off from the reaction vessel under reduced pressure to obtain 35.1 g of a TAIC polymer (hereinafter referred to as "TAIC polymer 4") as a pale yellow viscous liquid.
[0073] <measurement> Using the above-mentioned measurement methods, the viscosity, mass average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn), decomposition temperature, dielectric constant, dielectric loss tangent, and volatile content of TAIC polymer 4 were measured. The results are shown in Table 1.1 H NMR measurement results ( 1 1 H NMR spectrum) is shown in Figure 4.
[0074] [Example 5] Synthesis of TAIC polymer Mo(N-2,6-iPr 2 C 6 H 3 )(CHCMe 2 Ph)(OCMe(CF 3 ) 2 ) 2 (62.2 mg, 0.0813 mmol) was weighed into a two-necked recovery flask, and toluene (3 mL) was added to prepare a catalyst solution. TAIC (35.7 g, 143 mmol) was weighed into another two-necked eggplant flask, toluene (5 mL) was added, and then tri-n-octylaluminum (0.070 mmol) was added and stirred to prepare a raw material solution. The catalyst solution was added to the raw material solution, and the mixture was stirred at 40°C for 55 minutes. After stirring, benzaldehyde was added to the reaction solution to quench the reaction. After the reaction was stopped, toluene was distilled off from the reaction vessel under reduced pressure to obtain 34.0 g of a TAIC polymer (hereinafter referred to as "TAIC polymer 5") as a pale yellow viscous liquid.
[0075] <measurement> Using the above-mentioned measurement methods, the viscosity, mass average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn), decomposition temperature, dielectric constant, dielectric loss tangent, and volatile content of TAIC polymer 5 were measured. The results are shown in Table 1. 1 H NMR measurement results ( 1 1 H NMR spectrum) is shown in Figure 5.
[0076] [Comparative Example 1] Using the TAIC, the viscosity, dielectric constant, dielectric loss tangent, and volatile content were measured and evaluated by the above-mentioned measurement method. The results are shown in Table 2. 1 The results (spectrum) of the H NMR measurement are shown in FIG. Incidentally, since the material evaporated during the measurement of the decomposition temperature, it was not possible to measure the decomposition temperature by the above-mentioned measuring method.
[0077] [Table 1]
[0078] [Table 2]
[0079] [Results explanation] In Examples 1 to 5, it was shown that the TAIC polymer of the present invention has a decomposition temperature of 400° C. or higher, exhibits excellent heat resistance, and has a volatile content of 50 mass % or less, exhibits low volatility. The dielectric constants and dielectric tangents of Examples 1 to 5 are preferably smaller, but are equivalent to those of Comparative Example 1, demonstrating that the TAIC polymer of the present invention has dielectric properties that compare favorably with conventional TAIC. From the above, the TAIC polymer of the present invention can be applied to or impregnated into a substrate in a liquid state, has suppressed volatility, and has excellent heat resistance. In addition, the TAIC polymer of the present invention has dielectric properties that are within 70 to 130% of those of conventional TAIC, and is therefore considered to be able to replace TAIC. [Industrial Applicability]
[0080] The TAIC polymer of the present invention can achieve both a high dielectric constant and low volatility. Furthermore, it has high heat resistance and can be applied to crosslinking reactions at high temperatures. It can be used in place of conventional TAIC and can be applied to prepregs, etc.
Claims
1. It is liquid at 30°C and has a viscosity at 300 mPa·s or more, A triallyl isocyanurate polymer, in which signals (peaks) are observed at 4.5 to 5.0 ppm and 5.4 to 5.8 ppm in a 1 H-NMR spectrum measured at a measurement temperature of 30° C. using deuterated chloroform as a solvent.
2. The polystyrene-equivalent weight average molecular weight (Mw) measured by gel permeation chromatography is 480 or more, A triallyl isocyanurate polymer, in which signals (peaks) are observed at 4.5 to 5.0 ppm and 5.4 to 5.8 ppm in a 1 H-NMR spectrum measured at a measurement temperature of 30° C. using deuterated chloroform as a solvent.
3. A triallyl isocyanurate polymer that is liquid at 30°C and has a viscosity at 30°C of 300 mPa·s or more, and has a structure represented by formula (2). 【Chemistry 1】 In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represent a hydrogen atom or a hydrocarbon group which may contain a heteroatom; m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; When n≠0, L 1 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, and when n=0, L 1 represents a divalent group represented by formula (a). 【Chemistry 2】 In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, and R 9 and R 10 each independently represent a hydrogen atom or a hydrocarbon group which may contain a heteroatom.
4. A triallyl isocyanurate polymer having a polystyrene-equivalent mass average molecular weight (Mw) of 480 or more as measured by gel permeation chromatography and a structure represented by formula (2): 【Chemistry 3】 In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represent a hydrogen atom or a hydrocarbon group which may contain a heteroatom; m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; When n≠0, L 1 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, and when n=0, L 1 represents a divalent group represented by formula (a). 【Chemistry 4】 In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, and R 9 and R 10 each independently represent a hydrogen atom or a hydrocarbon group which may contain a heteroatom.
5. The triallyl isocyanurate polymer according to claim 1 or 2, having a structure represented by formula (2). 【Chemistry 5】 In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom, m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; L 1 represents a tetravalent linking group containing two divalent linking groups derived from double bonds or carbon-carbon double bonds when n≠0, and represents a divalent group represented by formula (a) when n=0. 【Chemistry 6】 In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, R 9 and R 10 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom.
6. A triallyl isocyanurate polymer represented by formula (2): 【Chemistry 7】 In formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom, m is an integer of 1 or more, n is an integer of 0 or more, and m and n satisfy 3≦m+n≦10; L 1 represents a tetravalent linking group containing two divalent linking groups derived from double bonds or carbon-carbon double bonds when n≠0, and represents a divalent group represented by formula (a) when n=0. 【Chemistry 8】 In formula (a), L 2 represents a double bond or a tetravalent linking group containing two divalent linking groups derived from a carbon-carbon double bond, R 9 and R 10 each independently represents a hydrogen atom or a hydrocarbon group which may contain a heteroatom.
7. A method for producing a triallyl isocyanurate polymer by polymerizing triallyl isocyanurate by an olefin metathesis reaction, comprising the steps of: The method for producing a triallyl isocyanurate polymer, wherein the triallyl isocyanurate polymer is liquid at 30° C. and has a viscosity at 30° C. of 300 mPa·s or more.
8. A method for producing a triallyl isocyanurate polymer by polymerizing triallyl isocyanurate by an olefin metathesis reaction, comprising the steps of: The method for producing a triallyl isocyanurate polymer, wherein the triallyl isocyanurate polymer has a polystyrene-equivalent mass average molecular weight (Mw) of 480 or more as measured by gel permeation chromatography.
9. The method for producing triallyl isocyanurate polymer according to claim 1 or 2, wherein triallyl isocyanurate is polymerized by an olefin metathesis reaction.
10. A curable composition comprising the triallyl isocyanurate polymer according to any one of claims 1 to 6 and a crosslinkable polymer.
11. A polymer molded article obtained by curing the curable composition according to claim 10.
Citation Information
Patent Citations
Novel di*isocyanuro* compound
JP1979103881A
Preparation of para-tertiary-butylphenol
JP1983052234A
Production of triallyl isocyanurate polymer
JP1990300232A
Production of triallyl isocyanurate prepolymer
JP1992057803A
Photocurable resin composition
JP2001026608A